The City Otherwise - Korkina, Elena (project baikal, 2017)
The City Otherwise (From Rus. Gorod Inache) is a research project focused on modern Irkutsk. The offline part of the project includes lectures, courses, workshops and other events concerning Irkutsk. The online one is the website gorodinache.org consisting of two sections: “Research” and “Impression”. The first section presents social and art research publications on the daily life, citizens’ practice, Irkutsk landmarks etc. The second one contains impressions of Irkutsk.The goals of the project are:– to develop the interest toward modern Irkutsk and to support the willingness to understand its nature;– to make the life in the city brighter on a self-sustainable basis;– to form a community willing to work on new collaborative city projects.At the initial stage (working out the concept, the first research and impressions, development of the website), the project was international. We collaborated with the German non-governmental organization Froh! specializing in adult education. In September 2016 we organized a two-week workshop, where we worked on photos, digital layout, texts etc. From the beginning of 2017, the Irkutsk team has been working on the project independently.Our authors are those who are interested in Irkutsk, or rather in a certain issue related to Irkutsk. The first 18 works were elaborated by 20 authors from Irkutsk and Germany. All of them were selected on a competitive basis. At this moment we are working on a new research together with all interested people, as usual, regardless of age, profession, research background or place of residence. The main thing is their willingness to search for new solutions and forms together with the project team.
Keywords: Irkutsk; social research; local community; daily life; media; city projects; participation